(3HjGf GdNdGaGJ aj Mb GHf GdYQHis - (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s ((3YHO GdQMef Hf TQja s)
(3ChdgG (B:s
(3GdMeO ddg fGUQ GdMb ENJda GdfGS ai GHf YQHi UGMH GdaUhU aGdLeghQ ef CFeI SGFQ GdePGgH Phi GdfbO hGdMaX LfMhG Edi GdNW Ydjg hJbHjMg Ch JcajQg s
(3BNQgG (B:s
(3hCeG GdTjN YHO Gddg GdeJhai agh eY PeI dg cGf jWGdY GdaJhMGJ hjShi HjfgG hHjf GdcTGa dETJeGdgG Ydi daJ hGdSejf hdcf bO hQO Pdc GdJbi GdSHci hbQQ GdaQb HjfgeG HeG HjfGg ai GdCUd CdgefG Gddg QTOfG JeJ gPg GdQSGdI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B150s
Keywords: (3GdJhMjO hGdedd hGdfMds